Películas y series televisivas en la enseñanza de la ética médica - García-Berrocal, Jorge; Zambrano-Huailla, Alexander; Zambrano-Huailla, Rommel; Zavala-Flores, Ernesto; Montes-Alvis, José (Revista Médica Herediana, 2014)
.